Mechanical Property of 9 Years Old Thinning of Teak Plantation in Thailand - Somchai Seviset; Thanate Piromgran; Udomsak Saributr; Ratthai Porncharoen; Kananke Raerai; Sittichai Charoensettasilp (My University, 2017)
Based on the study of the conditions and problems of thinned teak in Thailand it's with findings that thinned teak or so called thinning for distance clearance being with small stems and can be sold at low price. thinned teak was with mechanical property different with teak from natural forest with age over 30 years old with the results of most of the tests were with findings that the values of the mechanical property of teak from natural forest with age over 30 years were more valuable than the values of the mechanical properties of thinned teak with exception on Standard Test Method for Tensile and Cleavage Test of Timber which thinned teak was with more value than teak from natural forest with age over 30 years old. For guidelines on market value added for thinned teak can be made by producing to use in the context of the design of household goods made of wood as the guide for resolution of problems and creation of artistic work pieces household goods made of wood.
Keywords: Thinning; Natural forest; Structural Engineering and Vibration Analysis